The Routledge companion to design studies - Sparke, Penny; Fisher, Fiona (Abingdon, Oxon Routledge, 2016)
Since the 1990s, in response to dramatic transformations in the worlds of technology and the economy, design - a once relatively definable discipline, complete with a set of sub-disciplines - has become unrecognizable. Consequently, design scholars have begun to address new issues, themes and sub-disciplines such as: sustainable design, design for well-being, empathic design, design activism, design anthropology, and many more.

The Routledge Companion to Design Studies charts this new expanded spectrum and embraces the wide range of scholarship relating to design - theoretical, practice-related and historical - that has emerged over the last four decades.

Comprised of forty-three newly-commissioned essays, the Companion is organized into the following six sections: defining design: Discipline, Process Defining Design: Objects, Spaces Designing Identities: Gender, Sexuality, Age, Nation Designing Society: Empathy, Responsibility, Consumption, the Everyday Design and Politics: Activism, Intervention, Regulation Designing the World: Globalization, Transnationalism, Translation Contributors include both established and emerging scholars and the essays offer an international scope, covering work emanating from, and relating to, design in the United Kingdom, mainland Europe, North America, Asia, Australasia and Africa. This comprehensive collection makes an original and significant contribution to the field of Design Studies.
Keywords: Design